Effect of Surface Treated Nanofillers on Abrasive Wear of Carbon Fiber/Polyamide Blend Composites - S. Srinivas; R. Hemanth; B. Harshavardhan; G. S. Ananthapadmanabha; B. Suresha (Tribology in Industry)
This work investigated the fabrication and wear behaviour of a carbon fiber reinforced polyamide (cf/PA) blend composite with silane-treated graphene and silica nanoparticles. Using an extrusion and injection molding process, four series of cf/PA blend composites with different concentrations of silica and graphene (0 to 3 wt%) were made from a polyamide blend consisting of PA6 and thermoplastic copolyester (80:20). To evaluate two-body abrasive wear, 320 grit silicon carbide emery paper and a pin-on-disk wear test apparatus were utilized. The test results showed that the specific wear rate (SWR) decreased regardless of the type of nanofiller used. Tiny quantities of nanofillers treated with silane improve filler-matrix adhesion and increase the abrasion resistance of hybrid composites. The hybrid composite consisting of dual nanoparticles (each 1.5 wt%) into cf/PA revealed a significant decrease in SWR. To identify the wear mechanisms, a scanning electron microscope was used to study the worn surfaces of the selected composite samples. To sum up, the use of surface-treated nanofillers significantly enhances the abrasion resistance of cf/PA blend composites. The findings underscore the potential for further developments in composite material technology, which will have an impact on a variety of industries, including aerospace and automotive, where there is a growing need for materials that are both strong and lightweight.